Extrinsic nature of the broad photoluminescence in lead iodide-based Ruddlesden–Popper perovskites - Simon Kahmann (Nature Portfolio, 2020)
The Ruddlesden–Popper type of halide perovskites are gaining interest but the origin of their broad band emission remains elusive. Here Kahmann et al. suggest that in-gap states, instead of the commonly believed self-trapped excitons, are responsible for the broad band emission in crystalline samples.